Pengaruh Return On Asset, Sales Growth, Dan Financial Lease Terhadap Tax Avoidance (Studi Pada Perusahaan Manufaktur Sub Sektor Otomotif Yang Terdaftar Di BEI) - Dewa Ayu Putu Rahyuni; Nyoman Karna (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
As the largest source of state revenue, government always seek to optimize tax revenue. However, on the other hand, taxpayers also trying to do tax planning to minimize their tax obligation. As example, several manufacturing companies applied tax planning schemes in the form of tax avoidance so as not to violate tax laws but able to minimize their tax. This research aims to analyse the factors that affect the tax avoidance including return on asset, sales growth, and financial lease in automotive manufacturing sub-sector listed in Indonesia Stock Exchange in 2010-2016 period. For the research method, this research uses quantitative method approach and the sampling technique used is purposive sampling technique. The sample in this research uses 30 manufacturing companies within 7 years period to obtain as many as 84 data. For data analysis, this research uses panel data regression approach using EViews 9.0 software. The study shows that return on asset, sales growth and financial lease have the influence to do tax avoidance practice of 25.774% and the other 74.226% is influenced by other variable outside this study. The analysis result shows that return on asset, sales growth and financial lease simultaneously influenced manufacturing companies to do tax avoidance. Partially, return on asset affects the manufacturing companies to do tax avoidance, while sales growth and financial lease does not. Keywords: Return On Asset, Sales Growth, Financial Lease, Tax Avoidance